Bone morphogenetic protein 7 sensitizes O6-methylguanine methyltransferase expressing-glioblastoma stem cells to clinically relevant dose of temozolomide. Issue 1 (December 2015) - Tso, Jonathan; Yang, Shuai; Menjivar, Jimmy; Yamada, Kazunari; Zhang, Yibei; Hong, Irene; Bui, Yvonne; Stream, Alexandra; McBride, William; Liau, Linda; Nelson, Stanley; Cloughesy, Timothy; et al.
Abstract Background Temozolomide (TMZ) is an oral DNA-alkylating agent used for treating patients with glioblastoma. However, therapeutic benefits of TMZ can be compromised by the expression of O6-methylguanine methyltransferase (MGMT) in tumor tissue. Here we used MGMT-expressing glioblastoma stem cells (GSC) lines as a model for investigating the molecular mechanism underlying TMZ resistance, while aiming to explore a new treatment strategy designed to possibly overcome resistance to the clinically relevant dose of TMZ (35 μM). Methods MGMT-expressing GSC cultures are resistant to TMZ, and IC50 (half maximal inhibitory concentration) is estimated at around 500 μM. Clonogenic GSC surviving 500 μM TMZ (GSC-500 μM TMZ), were isolated. Molecular signatures were identified via comparative analysis of expression microarray against parental GSC (GSC-parental). The recombinant protein of top downregulated signature was used as a single agent or in combination with TMZ, for evaluating therapeutic effects of treatment of GSC. Results The molecular signatures characterized an activation of protective stress responses in GSC-500 μM TMZ, mainly including biotransformation/detoxification of xenobiotics, blocked endoplasmic reticulum stress-mediated apoptosis, epithelial-to-mesenchymal transition (EMT), and inhibited growth/differentiation. Bone morphogenetic protein 7 (BMP7) was identified as the top down-regulated gene in GSC-500 μM TMZ. Although augmenting BMP7 signaling in GSC by exogenous BMP7 treatment did not effectively stop GSC growth, it markedly sensitized both GSC-500 μM TMZ and GSC-parental to 35 μM TMZ treatment, leading to loss of self-renewal and migration capacity. BMP7 treatment induced senescence of GSC cultures and suppressed mRNA expression of CD133, MGMT, and ATP-binding cassette drug efflux transporters (ABCB1, ABCG2), as well as reconfigured transcriptional profiles in GSC by downregulating genes associated with EMT/migration/invasion, stemness, inflammation/immune response, and cell proliferation/tumorigenesis. BMP7 treatment significantly prolonged survival time of animals intracranially inoculated with GSC when compared to those untreated or treated with TMZ alone (p  = 0.0017), whereas combination of two agents further extended animal survival compared to BMP7 alone (p  = 0.0489). Conclusions These data support the view that reduced endogenous BMP7 expression/signaling in GSC may contribute to maintained stemness, EMT, and chemoresistant phenotype, suggesting that BMP7 treatment may provide a novel strategy in combination with TMZ for an effective treatment of glioblastoma exhibiting unmethylated MGMT.